2022
DOI: 10.3390/healthcare10102108
|View full text |Cite
|
Sign up to set email alerts
|

Religious Affiliation and Flu Vaccination in Germany: Results of the German Ageing Survey

Abstract: Our aim was to examine the association between religious affiliation and the likelihood of taking the flu vaccine. Cross-sectional data (year 2014 with n = 7172) were used from the nationally representative German Ageing Survey—covering community-dwelling individuals aged 40 years and over. Multiple logistic regressions showed that compared with individuals without a religious affiliation, individuals with certain religious affiliations had a lower likelihood of taking the flu vaccine. More precisely, the like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Religious beliefs have been significantly associated with immunization inequality in low-, middle-and high-income countries [32]. A recent study revealed that religious affiliation and the likelihood of receiving a certain vaccine were significantly correlated in Germany [33]. In addition, deprived groups, such as ST people in India, were more likely to live in remote areas with limited immunization facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Religious beliefs have been significantly associated with immunization inequality in low-, middle-and high-income countries [32]. A recent study revealed that religious affiliation and the likelihood of receiving a certain vaccine were significantly correlated in Germany [33]. In addition, deprived groups, such as ST people in India, were more likely to live in remote areas with limited immunization facilities.…”
Section: Discussionmentioning
confidence: 99%